2022
DOI: 10.1186/s12876-022-02334-6
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal fatty acid binding protein is a disease biomarker in paediatric coeliac disease and Crohn’s disease

Abstract: Background There is a clinical need to develop biomarkers of small bowel damage in coeliac disease and Crohn’s disease. This study evaluated intestinal fatty acid binding protein (iFABP), a potential biomarker of small bowel damage, in children with coeliac disease and Crohn’s disease. Methods The concentration iFABP was measured in plasma and urine of children with ulcerative colitis, coeliac disease, and Crohn’s disease at diagnosis and from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Serum biomarkers are particularly important where both skin and gut are affected in the disease pathogenesis or manifestation. For example, fatty acid binding proteins, which are serum biomarkers of inflammation and epithelial barrier dysfunction ( Baran et al., 2019 ; Lee et al., 2021 ), are important factors in both skin and gut involvement ( Logan et al., 2022 ; Yin et al., 2022 ), and they may serve as early predictors of SkAE following anti-TNF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Serum biomarkers are particularly important where both skin and gut are affected in the disease pathogenesis or manifestation. For example, fatty acid binding proteins, which are serum biomarkers of inflammation and epithelial barrier dysfunction ( Baran et al., 2019 ; Lee et al., 2021 ), are important factors in both skin and gut involvement ( Logan et al., 2022 ; Yin et al., 2022 ), and they may serve as early predictors of SkAE following anti-TNF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…After the intestinal mucosa is damaged, I-FABP quickly enters the blood circulation through the cell membrane, capillaries, lymphatic capillaries, and portal vein (7). Therefore, the levels of I-FABP in the blood reflect the degree of intestinal mucosal damage (8).…”
Section: Introductionmentioning
confidence: 99%
“…5 In another study, urinary and plasma I-FABP were assessed among 138 children with IBD and CeD (47 with CD, 11 with UC, 12 with newly diagnosed CeD, 40 with established CeD and 28 without IBD or CeD), plasma I-FABP levels were significantly higher in the children with newly diagnosed CeD and those with CD only when compared to those without IBD or CeD. 10 Otherwise, urinary and plasma I-FABP levels did not differ between the rest of the groups, which is consistent with the results in the current study. The present study was limited by small sample size with predominately patients with CD of mild disease severity and other available biomarkers, such as fecal calprotectin, were not available for comparison.…”
mentioning
confidence: 99%
“…A recent study found that urinary I-FABP levels fall in young adults with active CD following 8 weeks of exclusive enteral nutrition, suggesting that it may be a sensitive indicator of disease activity [ 5 ]. In another study, urinary and plasma I-FABP were assessed among 138 children with IBD and CeD (47 with CD, 11 with UC, 12 with newly diagnosed CeD, 40 with established CeD and 28 without IBD or CeD), plasma I-FABP levels were significantly higher in the children with newly diagnosed CeD and those with CD only when compared to those without IBD or CeD [ 10 ]. Otherwise, urinary and plasma I-FABP levels did not differ between the rest of the groups, which is consistent with the results in the current study.…”
mentioning
confidence: 99%